Functional diversity of bacteria in various saline soil plant vegetations around Sialang Buah Coast, North Sumatra, Indonesia - Mariani Sembiring; Juli M. Hutahuruk; Dwi Ningsih Susilowati; Erny Yuniarti; T. Sabrina; Luthfi A. Mahmud Siregar (Sains Tanah: Journal of Soil Science and Agroclimatology)
Environmental conditions profoundly influence microbial diversity and activity in soil. For optimal growth, soil microbes face limiting factors such as temperature, moisture, pH, and salinity levels. This study aims to find types of functional bacteria that are able to live in saline soils. The study was conducted in the Soil Biology Laboratory at Universitas Sumatera Utara (USU), Indonesia. Soil samples were collected around the Sialang Buah Coast, Serdang Bedagai Regency, North Sumatra, Indonesia. The method employed in this research was random composite sampling taken from three vegetation types: mangrove forests, grasslands, and oil palm plantations, with sample collection locations influenced by tidal fluctuations. Ten sampling points were taken at each location and then composited for each vegetation type. The results of the study showed that there were ten species of bacteria that were able to live in saline soil, namely Pseudomonas aeruginosa, Burkholderia gladioli, Enterobacter cloacae, Brucella ciceri, Ochrobactrum oryzae, Achromobacter xylosoxidans, Priestia flexa, Enterobacter quasiroggenkampii, Bacillus cereus and Ochrobactrum oryzae. All bacteria found were able to grow on Pikovskaya, Alexandrov, and Jensen media and only seven species of bacteria were able to form biofilms, namely P. aeruginosa, B. gladioli, E. cloacae, B. ciceri, A. xylosoxidans, P. flexa, and E. quasiroggenkampii